2007
DOI: 10.1152/jn.01333.2006
|View full text |Cite
|
Sign up to set email alerts
|

Verticality Perception During Off-Vertical Axis Rotation

Abstract: During prolonged rotation about a tilted yaw axis, often referred to as off-vertical axis rotation (OVAR), a percept of being translated along a conical path slowly emerges as the sense of rotation subsides. Recently, we found that these perceptual changes are consistent with a canal–otolith interaction model that attributes the illusory translation percept to improper interpretation of the ambiguous otolith signals. The model further predicts that the illusory translation percept must be accompanied by slowly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Studies (Vingerhoets et al 2006, 2007) have reported that human translation perception during off-vertical axis rotation (OVAR) can be modeled by adding a leaky integrator (time constant of 40 ms) to Merfeld’s model (Merfeld and Zupan 2002) to convert estimated linear acceleration to estimated linear velocity. Another model includes internal models and dynamics similar to those discussed above but additionally includes the influence of dynamic visual cues (Zupan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies (Vingerhoets et al 2006, 2007) have reported that human translation perception during off-vertical axis rotation (OVAR) can be modeled by adding a leaky integrator (time constant of 40 ms) to Merfeld’s model (Merfeld and Zupan 2002) to convert estimated linear acceleration to estimated linear velocity. Another model includes internal models and dynamics similar to those discussed above but additionally includes the influence of dynamic visual cues (Zupan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A small out-the-window-view of the stars passing by will play a minor role in orientation perception, and as a result, astronauts will be forced to depend significantly on their vestibular system and the cockpit displays. For each of the simulations performed in this paper, the gains were determined from data from simple human perception experiments [8,17].…”
Section: Methodsmentioning
confidence: 99%
“…Within these models the general framework is defined theoretically and then the set of gains is adjusted to help the model fit experimental test cases [8,17,18].…”
Section: Observer Modelmentioning
confidence: 99%
“…This “Observer” head orientation estimation scheme is arguably optimal in a Bayesian/Kalman sense (Selva and Oman 2012). Observer models for head and eye movement have since been employed to interpret a variety of human and animal vestibular experimental data (Merfeld et al 1993; Haslwanter et al 2000; Merfeld and Zupan 2002; Vingerhoets et al 2007) as well as to model human reaching movements (Wolpert et al (1995); (1998)). Notably, Wolpert and colleagues argued that the cerebellum contained internal “forward” models used to predict the sensory consequences of motor commands and thereby compensate for time delays (see also Ito (1970).…”
Section: Sensory Conflict Hypothesesmentioning
confidence: 99%